In the Acute Phase of Trypanosoma cruzi Infection, Liver Lymphoid and Myeloid Cells Display an Ambiguous Phenotype Combining Pro- and Anti-Inflammatory Markers - de Lima Pereira dos Santos, Carina; Vacani-Martins, Natalia; Cascabulho, Cynthia Machado; Pereira, Mirian Claudia de Souza; Crispe, Ian Nicholas; Henriques-Pons, Andrea (Frontiers in Immunology, 2022)
Multiple cell populations, cellular biochemical pathways, and the autonomic nervous system contribute to maintaining the immunological tolerance in the liver. This tolerance is coherent because the organ is exposed to high levels of bacterial pathogen-associated molecular pattern (PAMP) molecules from the intestinal microbiotaflora, such as lipopolysaccharide endotoxin (LPS). In the case of Trypanosoma cruzi infection, although there is a dramatic acute immune response in the liver, we observed intrahepatic cell populations combining pro- and anti-inflammatory markers. There wasWe observed a During Trypanosoma cruzi infection a dramatic immune response occurs in the liver. There is loss of fully mature Kupffer cells and an increase in other myeloid cells, which are likely to include monocytes. Among dendritic cells (DCs), the cDC1 population expandeds relative to the others, and these cells loste both some macrophage markers (F4/80) and immunosuppressive cytokines (IL-10, TGF-B1). In parallel, a massive T cell response occureds with loss of naïve cells and increases in several post-activation subsets. However, these activated T cells expressed both markers programmed cell death protein (PD-1) and cytokines consistent with immunosuppressive function (IL-10, TGF-1). NK and NK-T cells broadly followed the pattern of T cell activation, while TCR-gd cells appeared to be bystanders. While no data were obtained concerning IL-2 and IFN-, several cell populations also synthesized IFN-γ and TNF-a, which has been linked to host defense but also to tissue injury. It therefore appears that T. cruzi exerts control over liver immunity, causing T cell activation via cDC1 but subverting multiple populations of T cells into immunosuppressive pathways. In this way, T. cruzi engages a mechanism of hepatic T cell tolerance that is familiar from liver allograft tolerance, in which activation and proliferation are followed by T cell inactivation.